(untitled) (Jagannath University Journal of Science, 2024)
A specially designed, named Dynamic Aurora pulsed laser deposition (PLD) has been developed to in situ grow thin films in a magnetic field up to 2000 G. Spontaneous superlattice formation occurs in the case of perovskite structure ceramics due to the application of magnetic field during thin films deposition. In this study, we examine the possibility and optimize the conditions of spontaneous superlattice formation in the case of fluorite structure, stabilized zirconia thin films under in situ magnetic field grown by Dynamic Aurora PLD. Although, a superlattice structure was not formed in this fluorite material system. To explain this discrepancy, several factors can be considered such as the number of the cation sites in the crystal structure. Perovskite structure has two cation sites, while the fluorite structure has only one cation site. This study provides necessary information for further research in developing self-organized superlattice structure synthesis techniques under magnetic-field associated pulsed laser deposition technique and simultaneously, also can play important roles in the processing of another materials system. Jagannath University Journal of Science, Volume 10, Number I, Jun. 2023, pp. 55-63